Ellimenistes humeralis Marshall, 1947 and its allies (Coleoptera: Curculionidae: Entiminae: Embrithini) - Borovec, Roman; Nakládal, Oto (Zootaxa, 2019)
The Ellimenistes humeralis Marshall, 1947 species group is defined. Ellimenistes humeralis is redescribed, three new species belonging to this species group are described, illustrated and keyed: E. janaki Borovec & Nakládal, sp. nov., E. marshalli Borovec & Nakládal, sp. nov. and E. raucus Borovec & Nakládal, sp. nov., all from South Africa, Eastern Cape. A lectotype of Ellimenistes humeralis Marshall, 1947 is designated. The diagnosis of the genus Ellimenistes is completed with illustrations of the female genitalia provided for the first time.